CHALLENGES AND POTENTIALITIES IN MATERNAL AND CHILD CARE: PROMOTING COMPREHENSIVENESS AND REDUCING HARM - da Silva Izidoro, Jaqueline; Nayany do Nascimento Ferreira, Alejandra; Andrade Virginio de Oliveira, Annelissa; Rodrigues dos Santos, Leonardo; Eduardo Silva Araújo, Flavio; Ferreira Filgueiras, Thaynara; Gomes Lopes, Fabrícia; Carolina Salustino dos Santos, Maria (Revista Gênero e Interdisciplinaridade, 2026)
Maternal and child care is a strategic component of primary health care, with a strong impact on social and epidemiological indicators. This narrative review aims to reflect on the challenges and potentialities of maternal and child health care practices, emphasizing comprehensiveness and the prevention of harm. The selected articles revealed two thematic axes: the need to strengthen integrated care in primary health and the importance of multiprofessional and intersectoral practices in support networks. Evidence shows that fragmentation, lack of articulation between services, and the absence of qualified listening remain persistent barriers. On the other hand, experiences that invest in team training, active listening, and territorial engagement demonstrate transformative potential. It is concluded that maternal and child care requires integrated actions, sensitive to the sociocultural specificities of the served populations, and committed to promoting equity and human dignity from the beginning of life.